Evidence that the angiotensin IV (AT(4)) receptor is the enzyme insulin-regulated aminopeptidase - Albiston, A L; McDowall, S G; Matsacos, D; Sim, P; Clune, E; Mustafa, T; Lee, J; Mendelsohn, F A; Simpson, R J; Connolly, L M; Chai, S Y (The Journal of biological chemistry, 2001)
Central infusion of angiotensin IV or its more stable analogues facilitates memory retention and retrieval in normal animals and reverses amnesia induced by scopolamine or by bilateral perforant pathway lesions. These peptides bind with high affinity and specificity to a novel binding site designated the angiotensin AT(4) receptor. Until now, the AT(4) receptor has eluded molecular characterization. Here we identify the AT(4) receptor, by protein purification and peptide sequencing, to be insulin-regulated aminopeptidase (IRAP). HEK 293T cells transfected with IRAP exhibit typical AT(4) receptor binding characteristics; the AT(4) receptor ligands, angiotensin IV and LVV-hemorphin 7, compete for the binding of [(125)I]Nle(1)-angiotensin IV with IC(50) values of 32 and 140 nm, respectively. The distribution of IRAP and its mRNA in the brain, determined by immunohistochemistry and hybridization histochemistry, parallels that of the AT(4) receptor determined by radioligand binding. We also show that AT(4) receptor ligands dose-dependently inhibit the catalytic activity of IRAP. We have therefore demonstrated that the AT(4) receptor is IRAP and propose that AT(4) receptor ligands may exert their effects by inhibiting the catalytic activity of IRAP thereby extending the half-life of its neuropeptide substrates.